Coping with plagiarism and grading load: Randomized programming assignments and reflective grading - Spinellis, Diomidis; Zaharias, Panagiotis; Vrechopoulos, Adam (Computer applications in engineering education, 2007)
Programming assignments often suffer from plagiarism and lack of feedback. The Jarpeb system creates individually randomized assignments, grades the students' programs by utilizing Java's reflective evaluation capabilities, and allows students to submit their grade through the web by signing their grade with a cryptographically strong checksum. Jarpeb's empirical evaluation included as the dependent variables important learners' dimensions: plagiarism, understanding, learning, fairness, difficulty, fun, and interest. The results indicate that Jarpeb contributes to the reduction of plagiarism, increases the understanding, and learning of the course subject while also increasing the perceived fairness, fun, and interest of the learners. The system, however, proved to increase the difficulty of the related exercises. We discuss the implications for educators and outline specific future research directions. © 2007 Wiley Periodicals, Inc. Comput Appl Eng Educ. 15: 113–123, 2007; Published online in Wiley InterScience (www.interscience.wiley.com); DOI 10.1002/cae.20096